A prospective comparative study of levobupivacaine hydrochloride 0.5% with ropivacaine hydrochloride 0.75% for peri-operative epidural anesthesia in infra- umbilical surgeries - Shreya Putta; Satyendra Singh Yadav; Ankita Gupta; Rachna Gupta (Asian Journal of Medical Sciences)
Background: Epidural anesthesia is a neuraxial regional anesthesia used to provide surgical anesthesia, to supplement general anesthesia, and to provide intra and post-operative analgesia. Levobupivacaine and ropivacaine are local anesthetic agents used in an epidural.